2011
DOI: 10.1159/000325539
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cytogenetics and Molecular Phylogeography in the Group <i>Astyanax altiparanae – Astyanax </i>aff. <i>bimaculatus</i> (Teleostei, Characidae)

Abstract: The genus Astyanax comprises small characin fish of the neotropical region. The so-called ‘yellow-tailed characins’ compose one of the most widely distributed Astyanax groups. A. altiparanae and A. aff. bimaculatus, are evolutionarily closely related and commonly found in several Brazilian hydrographic basins. In the present work, chromosomal data of specimens of A. altiparanae and A. aff. bimaculatus from 4 hydrographic basins in the states of São Paulo (Upper Tietê, Paranapanema, Ribeira de Iguape) and Rio d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 86 publications
3
27
1
1
Order By: Relevance
“…Kavalco et al (2011) found monophyly in the A. altiparanae group, in agreement with the nominal redefinition proposed by Garutti and Britski (2000) for this species. However, when these authors analyzed the ND2 region of mtDNA, they found a possible paraphyly in the species that was attributable to sharing of haplotype groups between the Tietê and Paranapanema Basins.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Kavalco et al (2011) found monophyly in the A. altiparanae group, in agreement with the nominal redefinition proposed by Garutti and Britski (2000) for this species. However, when these authors analyzed the ND2 region of mtDNA, they found a possible paraphyly in the species that was attributable to sharing of haplotype groups between the Tietê and Paranapanema Basins.…”
Section: Discussionsupporting
confidence: 91%
“…The clustering between Astyanax sp (Iguaçu River) and A. fasciatus (Tibagi River) obtained in this study provides additional support for this hypothesis. According to Funk and Omland (2003), cryptic and taxonomically controversial species might interfere in the resolution of evolutionary trees; however, a polyphyletic condition might represent the real tree for the selected mitochondrial gene, and it might not be a simple artifact, depending on the branch-supporting values found in the tree (Kavalco et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As occur with C-bands, the genus Astyanax also shows distinct patterns in relation to NORs, with single and multiple systems and with both intra-and inter-specific variations in number and locations on the chromosomes (Kavalco and Moreira-Filho, 2003;Pazza et al, 2006;Capistano et al, 2008;Kavalco et al, 2011). In this study a multiple marking system was only found in Astyanax aff.…”
Section: Discussionmentioning
confidence: 44%
“…bimaculatus showed the same diploid number (2n=50) but with differences in the karyotype formulas, probably due to rearrangements such as pericentric inversions. This last group, unlike the "scabripinnis group", has shown a constancy in the diploid number (Domingues et al, 2007;Pamponet et al, 2008;Ferreira Neto et al, 2009;Kavalco et al, 2011;Pacheco et al, 2011;Peres et al, 2011;Martinez et al, 2012), indicating an evolutionary karyotype pattern relatively more conserved than that of the "scabripinnis complex". In turn, the distinct karyotypes presented by the two populations of A. asuncionensis also show the occurrence of two karyomorphs and a probable "asuncionensis complex."…”
Section: Discussionmentioning
confidence: 99%